2011
DOI: 10.1126/scisignal.2001993
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Phosphorylation Analysis of Human Mitotic Protein Complexes

Abstract: Progression through mitosis depends on a large number of protein complexes that regulate the major structural and physiological changes necessary for faithful chromosome segregation. Most, if not all, of the mitotic processes are regulated by a set of mitotic protein kinases that control protein activity by phosphorylation. Although many mitotic phosphorylation events have been identified in proteome-scale mass spectrometry studies, information on how these phosphorylation sites are distributed within mitotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 75 publications
(111 reference statements)
5
98
0
Order By: Relevance
“…S8). The synergistic action of these two phosphorylation events, possibly together with modifications on Pds5 and Wapl (29), may lead to opening of cohesin's exit gate (31)(32)(33), enabling release of cohesin from DNA. Sgo1-PP2A might inhibit this process at centromeres but also at some chromosomal arm sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S8). The synergistic action of these two phosphorylation events, possibly together with modifications on Pds5 and Wapl (29), may lead to opening of cohesin's exit gate (31)(32)(33), enabling release of cohesin from DNA. Sgo1-PP2A might inhibit this process at centromeres but also at some chromosomal arm sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, when mitotic cells were treated with Hesperadin or RO3360, as much Sororin was detected on chromatin as on chromatin from logarithmically proliferating cells. In contrast, Sororin dissociation was not reduced by BI 4834, although Plk1 was efficiently inhibited because the phosphorylation of SA2 on Ser1261, a residue known to be phosphorylated by Plk1 (20,29), was inhibited to the extent observed in logarithmically proliferating cells (Fig. 3A, WCE, whole-cell extract), and because cohesin dissociation from mitotic chromatin was reduced (Fig.…”
Section: Aurora B Activity Is Required For the Dissociation Of Sororimentioning
confidence: 95%
“…However, as the MS studies described above highlight [59 ,60 ], an additional appropriate data filter for prioritizing the functionally most relevant PTM-signals is interaction network context. The first large MS study measuring lysine-acetylation reported that acetylation accumulates over protein complexes in human cultured cells [71] and high phosphorylation levels were observed on specific subunits of mitotic complexes [72]. Supporting and extending this idea, a first computational analysis of global acetylation, phosphorylation and ubiquitylation data revealed that modifications cluster within interaction networks [66 ].…”
Section: Discussionmentioning
confidence: 92%
“…The conserved phosphorylation site is found to be Thr1415 of the CAP-D3 subunit of condensin II, whose phosphorylation then triggers recruitment of Plk1 to the chromosome axes through binding to CAP-D3 and thereby hyperphosphorylates the condensin II complex (1). The phospho-proteomics has been a powerful approach that provides comprehensive lists of protein phosphorylation (3,5,8). It is not necessarily straightforward, however, to link the information to cellular functional and/or structural significance.…”
mentioning
confidence: 99%